Exogenous Shocks, Deposit Runs and Bank Soundness : A Macroeconomic Framework - Blejer, Mario (IMF Working Papers; Working Paper, 1997)
In a model where all banks are initially solvent, an exogenous shock affects confidence, causing a flight from deposits into domestic and foreign currency. Real interest rates increase unexpectedly, affecting firms and raising the share of the banks' nonperforming assets. This increase causes genuine solvency problems and accelerates the bank run. Policy simulations show that compensatory monetary policy (increasing currency supply when deposits fall) mitigates the bank run but causes inflation and external imbalances. Combining compensatory monetary policy with tight fiscal policies also slows the bank run and mitigates insolvency, but at a lower macroeconomic cost. A devaluation is shown to have little positive impact.